PENDIDIKAN KARAKTER DALAM PROSES PEMBELAJARAN - Asra J.A Pakai (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This paper intends to describe character education in relation to the learning process. This research uses the library research method. Data collection in this study was carried out using a citation technique, namely quoting from various references related to the concept of character education and its relationship to the learning process. Data analysis by the author is carried out after the data is collected, the author analyzes in a methodical order and describes it using inductive-deductive reasoning. The curriculum contains learning materials or methods used by a teacher to students achieve the expected educational goals, then this curriculum produces a syllabus or lesson plan, or lesson plan. With the agreed learning plan, a teacher must be able to practice or implement character education in the learning process. One proof of the success of a teacher in implementing character education to students is that a student can connect the material obtained in class with real life